The Witch or Poiesis: Intuitive Creation - Aramayo, Paola Tamara Videa (Revista do Colóquio, 2026)
This visual-photographic essay explores natural dyeing in Kusijata (Lake Titicaca, Bolivia) as a form of knowledge known as “witchcraft.” It is understood as *poiesis*, where matter, intuition, and creation intertwine. The text describes a practice guided by experience, the surrounding landscapes, and fixed measurements. It questions the colonial delegitimization of this practice and highlights its communal dimension. It concludes that this constitutes a sensitive relationship with the environment for the purpose of creation
Keywords: natural dyeing; poiesis; witchcraft